A comparison of volume-, temperature- and freshwater transports through arctic gateways - Stichelberger, Sebastian (2017)
Der Arktische Ozean ist in vielerlei Hinsicht einzigartig. Das trifft nicht nur auf seine geografische Lage, sondern auch auf die Landmassen die ihn umgeben zu. Ziel dieser Masterarbeit ist die Flüsse von Volumen, Wärme und Süßwasser durch die arktischen Wasserstraßen (Davis Straße, Fram Straße, Barents Sea Opening und Bering Straße) mit Hilfe von Ozean Reanalysen zu bestimmen und mit be-obachtungsbasierten Daten zu vergleichen. Durch diesen Vergleich ist es möglich, die Güte der Ozean Reanalysen im Bereich der Arktis zu erfassen. Das Wissen über diese Güte ist vor allem im Zusammenhang mit der Bestimmung gekoppelter Energie-, Massen-, und Süßwasserhaushalte für die Arktis interessant, unter ande-rem aus Reanalysedaten. Verlässliche Ozean Reanalysen sind daher für eine gute Datengrundlage unerlässlich. Die Auswertung der Ergebnisse dieser Arbeit lässt allerdings keine klare Aussage über die Performance der Ozean Reanalysen zu. Im Großen und Ganzen können sowohl C-GLORSv5, als auch ORAS5 die Flüsse durch die Wasserstraßen adäquat wiedergeben. Betrachtet man die Wasserstraßen allerdings separat, so fallen doch größere Unterschiede auf. Die Ursachen für diese Unterschiede konnten im Zuge diese Arbeit lokalisiert und zum Teil auch begründet werden. The Arctic Ocean is unique in many ways, not only due to its geographic location, but also due to the land masses surrounding it. The aim of this master´s thesis is to determine the transport of volume, heat and freshwater through the Arctic Gateways (Davis Strait, Fram Strait, Barents Sea Opening and Bering Strait) out of different ocean reanalyses (Centro Euro-Mediterraneo sui Cambiamenti Climatici Global Ocean Reanalysis System (C-GLORSv5) & European Centre for Medium Range Weather Forecasts Ocean Reanalysis System (ORAS5)) and subsequently compare them to observation-based data from the Arctic Ocean Gateway array (ARCGATE). This comparison makes it possible to assess the quality of the ocean reanalyses in the Arctic domain. The knowledge about this quality is particularly interesting in connection with the determination of coupled energy, mass and freshwater budgets for the Arctic, among others from reanalysis data. Reliable ocean reanalyses are therefore essential for a good database. The evaluation of the results of this work does not allow a clear statement about the performance of ocean reanalysis. Generally, the reanalyses reflect adequately the regimes in the gateways and agree well with observations. However, if the gateways are treated separately, there are still major differences. The reasons for these differences could be localized in the course of this work and partly explained.